Knowledge of Premarital Couples Regarding Premarital Screening Thalassemia - Suciari Tri Utami; Niken Safitri Dyan Kusumaningrum (University of Muhammadiyah Malang, 2020)
Thalassemia is one of blood diseases that genetically inherited suffered by people worldwide, also in Indonesia. The number of people with thalassemia increases every year. Thalassemia could not be cured, however it can be prevented by early detection in premarital screening. The aim of this study was to describe knowledge of premarital couples regarding premarital screening thalassemia. This study was a quantitative research with a descriptive survey to premarital couples in KUA Tembalang, Semarang. The samples were determined purposively. The questionnaire of knowledge and attitude towards thalassemia and pre-marital screening was distributed to respondents, then analyzed descriptively. The result presented in the frequency and percentage. There were 71 couples participated in this study. The result showed that 75.4% of premarital couples have never heard about thalassemia. Only 46.5% of premarital couples have a good knowledge toward thalassemia. Moreover, 40.8% respondents know the right definition about screening. However, more premarital couples did not know that thalassemia could be prevented by premarital screening that they were. It is concluded that couples' knowledge about thalassemia and premarital screening thalassemia was still low. So, knowledge and understanding to thalassemia and early detection – premarital screening are important to ascertain individual status of thalassemia.